Mass production of a S-layer protein of Bacillus thuringiensis and its toxicity to the cattle tick Rhipicephalus microplus - Lormendez, Caleb C. (Sci Rep, 2019)
The most commonly used biopesticides to control agricultural, forest and insect vectors of human diseases are derived from the bacterium Bacillus thuringiensis, which begins to produce Cry and Cyt insecticidal proteins during the onset of the sporulation phase. Some B. thuringiensis strains also produce S-layer proteins that are toxic to certain pests. S-layer proteins are the most abundant proteins in bacteria and archaea. This proteins’ key trait to design high performace processes for mass production is their continuous expression during the vegetative phase, unlike Cry and Cyt, which are restricted to the sporulation phase. In this work, a S-layer protein expressed by the GP543 strain of B. thuringiensis that is toxic to the cattle tick Rhipicephalus microplus was mass produced using the batch culture fermentation technique. In addition, the spore-protein complex showed a mortality rate of 75% with a dose of 300 µg·mL(−1) on adult females of R. microplus after fourteen days. The lethal concentration 50 was 69.7 µg·mL(−1). The treatment also caused a decrease of 13% in the weight of the mass of oviposited eggs with 200 µg·mL(−1) of the spore-protein complex and inhibition of the hatching of eggs from 80 to 92%. Therefore, this could be a good option for controlling this parasite. The advantages of S-layer protein synthesis are focused on the production of a new generation of proteins in pest control. This is the first report on the mass production of an S-layer protein that is responsible for toxicity.